Performance Evaluation of Small Scale Air-Conditioning System Using R22 and Alternative Refrigerants (Journal of Engineering, 2014)
A mathematical model has been formulated to predict the influence of high outdoor air temperature on the performance of small scale air - conditioning system using R22 and alternative refrigerants R290, R407C, R410A. All refrigerants were investigated in the cooling mode operation. The mathematical model results have been validated with experimental data extracted from split type air conditioner of 2 TR capacity. This entailed the construction of an experimental test rig which consists of four main parts. They are, the refrigeration system, psychrometric test facility, measuring instrumentation, and auxiliary systems. The conditioned air was maintained at 25 0C dry bulb and 19 0C wet bulb for all tests. The outdoor ambient air temperature was varied from 35 0C to 55 0C in 5 0C increments. The study showed that R290 is the better replacement for R22 when the air conditioning system works under high ambient temperature. It has better performance as a drop in refrigerant. R407C has the closest performance to R22, followed by R410A.